AN ANALYSIS OF COHESIVE DEVICES IN ANALYTICAL EXPOSITION TEXT WRITTEN BY THE ELEVENTH GRADERS OF SMA N 1 MAGELANG IN THE SCHOOL YEAR 2016/2017 - Nilam Sari; Dwi Winarsih; Sri Sarwanti (Faculty of Education and Teachers Training, 2018)
This study investigates cohesive devices in analytical exposition text written by the eleventh graders of SMA N 1 Magelang in the school year 2016/2017. The objectives of this research are to know cohesive devices used and to know the type of cohesive devices mostly used in analytical exposition texts written by eleventh graders of SMA N 1 Magelang in the school year 2016/2017. This study applies descriptive qualitative research which consists of a detail linguistic description and explanation of cohesive devices in students‟ writing. The data were collected by note taking in the form of sentences. From the findings, it can be concluded that the analytical exposition texts analyzed in this research contain more grammatical cohesion rather than lexical cohesion. It is noticed that reference is mostly used in the texts and although the texts are somewhat cohesive, some parts still need improvement.